Indigenous Trauma Intervention Research in Canada: A Narrative Literature Review - Panofsky, Sarah; Buchanan, Marla J.; John, Roger; Goodwill, Alanaise (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2021)
Contemporary Indigenous mental health research is beginning to address colonization, contextualizing Indigenous health within a history of colonial relationships and inadequate mental health responses. In practice, however, dominant counselling models for mental health in Canada have neglected Indigenous perspectives and there is a paucity of research regarding interventions that address psychological trauma with Indigenous populations. We identified 11 Canadian studies that employed culturally appropriate trauma interventions within Indigenous communities. We discuss the findings in relation to the study participants, outcomes reported, and research design. Recommendations are provided to address the need for evidence-based trauma interventions that have efficacy for Indigenous people in Canada to address Indigenous historical trauma.